Balinese Art versus Global Art - Adrian Vickers (Pusat Kajian Bali Universitas Udayana, 2011)
AbstractThere are two reasons why “Balinese art” is not a global art form, firstbecause it became too closely subordinated to tourism between the 1950sand 1970s, and secondly because of confusion about how to classify“modern” and “traditional” Balinese art. The category of ‘modern’ artseems at first to be unproblematic, but looking at Balinese paintingfrom the 1930s to the present day shows that divisions into ‘traditional’,‘modern’ and ‘contemporary’ are anything but straight-forward. Indismantling the myth that modern Balinese art was a Western creation,this article also shows that Balinese art has a complicated relationship toIndonesian art, and that success as a modern or contemporary artist inBali depends on going outside the island.